Opportunities and challenges to integrating occupational safety, health, and well-being education into the United States undergraduate curricula. - Gallagher, Kaitlin M; Lueke, Sarah; Niu, Yuanlu (Work, 2025)
Background: To meet the demands and future of work in their field, Occupational Safety and Health (OSH) leaders in the United States call for curricula expansion; however, a complementary approach is to broaden the disciplines receiving OSH training. Objective: Provide examples and a discussion of how classes and modules on OHS and well-being can be taught in non-traditional disciplines in the United States. Methods: We present two case studies, one from a semester-long interdisciplinary course involving health and business students, and the other from a one-week module within an online management course, which provide different examples of how this content can be taught to undergraduate students. We then discuss future opportunities to integrate this into American undergraduate curricula. Results: Instructor-initiated education on OSH and well-being topics and were designed to foster situational interest and cultural humility in disciplines not typically receiving this content. The content was well received, and preliminary analyses of the assignment outcomes demonstrate pathways to success. Conclusions: There are many opportunities and challenges to mainstreaming OSH and well-being education across disciplines in American undergraduate curricula. We discuss the benefits of starting small, ideas for interdisciplinary modules, and considerations for face-to-face versus online offerings. Future work, including interviews with student alumnae and more detailed analyses of student content, will help inform future course offerings of this type.